Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Mary Louise Frampton in costume opening her rope to show wearing shiny tube top with back up singers Val Saldana, Robert Jones and Sam Vallis; In Background: Singer Lorraine Bolen and Tom Riche at keyboard Group: Rosie and the Supremes; a take-off on California Supreme Court Chief Justice Rose Bird